Effect of slatted floor type on performance of swine grown during cold - D Ames; D Brink (Kansas Agricultural Experiment Station Research Reports, 1974)
Average daily weight gain, feed consumption, and feed efficiency were determined for growing finishing swine reared on metal (aluminum) as opposed to plastic, slatted floor at ambient temperatures of 17, 32, 41 and 46 ÌŠ F. Performance was significantly (P<.05) improved with plastic slats at 17 and 32 F.; Swine Day, Manhattan, KS, November 14, 1974
Keywords: Swine day; 1974; Kansas Agricultural Experiment Station contribution; no. 483; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 221; Swine; Slatted floor type; Performance; Growth